Circus Maximus : The Economic Gamble Behind Hosting the Olympics and the World Cup - Zimbalist, Andrew S. (Book collections on Project MUSE., 2015)
Examines the impact of hosting major sporting events, including the World Cup and the Olympics, looking at the hollow claims given by private industry boosters and government supporters who promise an economic boon that never arrives.